2018
DOI: 10.1212/cpj.0000000000000421
|View full text |Cite
|
Sign up to set email alerts
|

Molecular genetic testing for hereditary ataxia

Abstract: Purpose of reviewBecause of extensive clinical overlap among many forms of hereditary ataxia, molecular genetic testing is often required to establish a diagnosis. Interrogation of multiple genes has become a popular diagnostic approach as the cost of sequence analysis has decreased and the number of genes associated with overlapping phenotypes has increased. We describe the benefits and limitations of molecular genetic tests commonly used to determine the etiology of hereditary ataxia.Recent findingsThere are… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
19
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(20 citation statements)
references
References 9 publications
1
19
0
Order By: Relevance
“…[1][2][3][4] The most common genetic ataxias, as well as several rarer forms, are caused by nucleotide repeat expansions, which typically require targeted non-sequencebased testing to identify. [5][6][7][8] Recent studies identified a recessive intronic (AAGGG) repeat expansion in replication factor C subunit 1 (RFC1) related to cerebellar ataxia, neuropathy, and vestibular areflexia syndrome (CANVAS) in Australia and the United Kingdom. 9,10 In addition, this expansion may be responsible for up to 22% (33/150) of sporadic cerebellar ataxia and 63% (32/51) of ataxia associated with sensory neuropathy.…”
mentioning
confidence: 99%
“…[1][2][3][4] The most common genetic ataxias, as well as several rarer forms, are caused by nucleotide repeat expansions, which typically require targeted non-sequencebased testing to identify. [5][6][7][8] Recent studies identified a recessive intronic (AAGGG) repeat expansion in replication factor C subunit 1 (RFC1) related to cerebellar ataxia, neuropathy, and vestibular areflexia syndrome (CANVAS) in Australia and the United Kingdom. 9,10 In addition, this expansion may be responsible for up to 22% (33/150) of sporadic cerebellar ataxia and 63% (32/51) of ataxia associated with sensory neuropathy.…”
mentioning
confidence: 99%
“…Friedrich's ataxia is diagnosed with genetic testing for trinucleotide repeat, 58 suspected in children and adolescents with profound gait abnormalities and possible family history.…”
Section: Chronic Pure Sensory Neuropathy/neuronopathymentioning
confidence: 99%
“…The most common etiologies overlap with those for DSP, specifically diabetes mellitus, vitamin abnormalities, and monoclonal gammopathy of unknown significance. An important comprehensive review 58 suggests the following tiered testing: an initial screen may include tests for diabetes mellitus or prediabetes with hemoglobin A1c, fasting glucose and 2-hour GTT, vitamin abnormalities with vitamin B12 level, and MMA and paraproteinemia with SPEP and IFE. Other initial tests may include triglyceride levels, thyroid-stimulating hormone, and vitamin B6, B1, and E. A second-line evaluation may include tests for SS-A and SS-B, Lyme's disease (ELISA or Western blot), sarcoidosis (serum ACE), heavy metals, and HIV, while a third-line evaluation may include amyloidosis (genetic testing or fat aspirate), Fabry's disease (α-galactosidase A assay), hepatitis C (virus antibody screening, ribonucleic acid confirmation if screen positive), leprosy (biopsy of the lesion), paraneoplastic disease (anti-Hu, anti-CV2/ collapsing response mediator protein 5, ANNA-3, anti-leucine-rich glioma inactive protein 1), acute intermittent porphyria (porphobilinogen in urine and erythrocytes), celiac disease (antigliadin antibodies), and other hereditary neuropathies (genetic testing).…”
Section: Small Fiber and Autonomic Neuropathymentioning
confidence: 99%
“…In the more than 100 described human hereditary ataxias, similar phenotypes can be caused by variants in different genes and different variants in the same gene can cause different phenotypes. 2 Described genetic variants, often in genes from conserved pathways, are repeat expansions, SNVs and INDELs, and follow a dominant, recessive, X-linked or mitochondrial inheritance. The prevalence of hereditary ataxias in humans varies in different populations, but ranges between 1-9 in 100 000 (ref.…”
Section: Introductionmentioning
confidence: 99%